MEASUREMENT OF ACCEPTANCE OF ONLINE ATTENDANCE SYSTEM WITH TECHNOLOGY ACCEPTANCE MODEL APPROACH: CASE IN DIRECTORATE GENERAL OF CHRISTIAN COMMUNITY, MINISTRY OF RELIGIOUS AFFAIRS OF THE REPUBLIC INDONESIA - Susana, Rahel; Lukman, Hendro (Graduate Program of Universitas Tarumanagara, 2023)
The purpose of this study is to analyze the attitude of user acceptance of online attendance at DirectorateGeneral of Christian Community Ministry of Religious Affairs Republic of Republic of Indonesia (RI) withTechnology Acceptance Model (TAM) approach. TAM is a method for analyzing acceptance of informationsystems. The population of this study are employees who use the online presence system in their daily present.The sampling technique used is simple random sampling. Total sample used is 60 samples. The data wasprocessed using SmartPLS version 3.0 with the Structural Equation Modeling (SEM) analysis method. Theresults of the analysis of this study found that Perceived Ease of Use (PEU) had a significant effect on perceivedusefulness (PU), Perceived Ease of Use (PEU) had a significant influence on Attitudes Toward Using (ATU)and Perceived Usefulness (PU) had significant effect on Attitude Toward Using (ATU). The implication of thisresearch is that it is necessary to develop a more informative attendance system and add other features in orderto improve employee performance at Ministry of Religious Affairs RI.